Characterization of homicides which occurred in a capital of a state of brazilian northeast: 2003 to 2007 - Tânia Silva Carvalho; Kélcia Kallyny Santana dos Santos; Adilma de Sousa Ferreira; Telma Maria Evangelista de Araújo; Adriana da Cunha Menezes Parente (Rev Rene)
This qualitative approach study has the aim to characterize the homicide cases registered in the city of Teresina-PI, from 2003 to 2007. Data were collected from death certificates (1.084) registered in the Medical Legal Institute- MLI in Teresina, PI and there was a discrepancy between the data obtained directly from these records the data presented by DATASUS, with higher values in all years, the first data. The results obtained showed a greater frequency among men (93.3%), single (72.5%), young adults (44.9%), students (19,3%), especially victims of firearm (52.7%). Moreover, the study showed a decrease in the number of homicides that occurred after the introduction of safety measures. This study may contribute to discussion and reflection of the approached them, that became a public health problem and generates great changes in society. Healthy professionals can assume a fundamental role on reduction of these deaths through preventive measures.